Effect of Audiovisual Media on the Level of Knowledge of Boarding Students of the West Sumatra Student Coaching and Sports Training Center about the Occurrence of Avulsion - Satria Yandi; Sri P. Utami; Nurma Yunika (e-GiGi, 2023)
Abstract: Dental trauma inter alia tooth avulsion is often found among athletes especially of contact sports. This study aimed to evaluate the effect of audiovisual media on the level of knowledge of boarding students of the West Sumatra Student Coaching and Sports Training Center about the occurrence of avulsion. This was a pre-experiment quantitative study with one group pretest-posttest design. The population were all athletes of the Center for Coaching and Sports Training of Students West Sumatera in soccer, athletics, sepak takraw, gymnastics, archery, bicycle, judo, karate, wrestling, boxing, taekwondo and pencak silat. There were 116 respondents obtained by using purposive sampling techniques. We used questionnaires as the research instrument. Data were analyzed with the Wilcoxon test. The results showed that the average knowledge before the the audio-visual media intervention was 10.39 and after the intervention was 12.43. The non-parametric Wilcoxon test showed a significancy of 0.000 (<0.05) which meant that there was an effect of audio-visual media intervention on the knowledge level of respondents. In conclusion, there is a significant effect of the audio-visual media intervention on the level of knowledge of the students of the West Sumatra Coaching and Sports Training Center about the occurrence of avulsion. Keywords: knowledge about dental trauma; tooth avulsion; audiovisual media; students of Coaching and Sports Training Center